2022
DOI: 10.1186/s12882-021-02636-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum Galectin-3 levels and all-cause and cardiovascular mortality in maintenance hemodialysis patients: a prospective cohort study

Abstract: Background Higher serum galectin-3 levels are related to adverse outcomes in different disease states. However, the association of galectin-3 with mortality in the maintenance hemodialysis (HD) population has not been fully described. Thus, we aimed to assess the predictive significance of galectin-3 for all-cause and cardiovascular (CV) mortality through a Chinese maintenance HD population. Methods A prospective cohort study was conducted in five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
12
1
Order By: Relevance
“…Galectin 3 is associated with inflammatory processes and myocardial fibrosis, being found to be present at the myocardial level after the onset of ischemia [ 73 ]. There are studies that have correlated increased levels of galectin 3 with increased mortality, including cardiovascular mortality, being considered an independent predictor in this regard [ 74 , 75 ]. A 2015 study found that elevated galectin 3 levels in hospitalized patients with heart failure confer an additional negative prognosis, but without predictive power of death [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Galectin 3 is associated with inflammatory processes and myocardial fibrosis, being found to be present at the myocardial level after the onset of ischemia [ 73 ]. There are studies that have correlated increased levels of galectin 3 with increased mortality, including cardiovascular mortality, being considered an independent predictor in this regard [ 74 , 75 ]. A 2015 study found that elevated galectin 3 levels in hospitalized patients with heart failure confer an additional negative prognosis, but without predictive power of death [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Galectin-3 is a relatively new biomarker that is well studied as a promoter of cardiac inflammation and fibrosis leading to heart failure [ 19 , 20 ]. In hemodialysis-treated patients, higher levels of galectin-3 seem to be associated with increased cardiac and all-cause mortality [ 21 , 22 , 23 ]. In our study, galectin-3 levels did not influence mortality during the two years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, galectin-3 levels did not influence mortality during the two years of follow-up. One should mention that the study by Liu on 506 HD patients showed that galectin levels above 8.65 ng/mL increased mortality, and the study by Hogas on 88 HD patients found a galectin-3 cut-off value of 23.73 ng/mL as an increased mortality risk [ 22 , 23 ]. The interesting result is that galectin-3 levels are negatively correlated with aortic valve fibrosis and mitral valve calcifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there was a positive correlation of serum Gal3 with neointima development (Ruan et al, 2021). In a prospective cohort study, higher serum Gal3 concentration was associated with a higher risk of cardiovascular mortality in patients receiving maintenance hemodialysis (hazard ratio (HR) = 2.13, 95% CI 1.07-4.26) (Liu et al, 2022). In addition, a cohort study of 2,477 participants showed that greater longitudinal increase in plasma Gal3 concentration was associated with increased incidence of heart failure and all-cause mortality (Ghorbani et al, 2018).…”
Section: Cardiovascular Events In Ckd and Esrdmentioning
confidence: 99%